An integrative perspective for CRMS implementation in healthcare in Malaysia - Baashar, Y.M. (Institute of Electrical and Electronics Engineers Inc., 2014)
Customer Relationship Management (CRM) is a powerful tool to help healthcare organizations in managing patient interactions. The further that the healthcare organizations understand the value of being customer-centric, the more likely they adopt to CRM as their main source of business strategy. Numerous of healthcare organizations are now practicing the CRM in order to computerize the medical processes and manage relationships with patients to deliver the best quality of medical services. Unfortunately, only few numbers of CRM projects have been successfully implemented, as the failure rate is said to be very high. In the Malaysian healthcare sector, the CRM concept has not acknowledged much attention and according to the review of literatures, there is a lack of CRM implementation and adoption in that field. In order to fill this gap and to improve the process of CRM implementation, this paper presents the investigation of CRMS implementation from an integration perspective. A mixed methodology of qualitative and quantitative and a study model that leads to CRMS implementation are proposed. Â© 2014 IEEE.